Thermodynamic Studies of Interaction Between Cetylrimethyl Ammonium Bromide and Lysozyme Using Potentiometric Techniques - Iloukhani, H.; Rafati, A.A.; Ravari, F. (Asian Journal of Chemistry, 2010)
The interaction between cetyltrimethyl ammonium bromide and lysozyme was studied by a potentiometric method using a surfactant- selective electrode. The binding isotherms of the interaction between cetyl trimethyl ammonium bromide were measured for different conditions and show a concentration dependence attributable to aggregation of the lysozyme-surfactant complexes. The binding isotherms are discussed in terms of the binding potential concept of Wyman and are used to calculate an apparent Gibbs energy of binding per surfactant cation.